2013
DOI: 10.3892/mmr.2013.1741
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA and gene networks in human Hodgkin’s lymphoma

Abstract: There has been significant progress in gene and microRNA (miRNA) research with regard to the morbidity of Hodgkin's lymphoma (HL). However, the regulatory mechanisms of genes and miRNAs have yet to be determined. In the current study, the regulatory association between genes, miRNAs and transcription factors (TFs) was investigated to gain an understanding of the mechanisms and key pathways of HL. The association between TFs and miRNAs, miRNAs and target genes and miRNA and its host gene was examined. To show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…These short RNAs may be extracted from blood in a non-invasive way, they are robust, survive treatment and endure prolonged storage conditions. Several studies involving the role of miRs in cHL have been reported [42][43][44][45][46][47][48], but very few in the context of an HIV-1 infection [49].…”
Section: Discussionmentioning
confidence: 99%
“…These short RNAs may be extracted from blood in a non-invasive way, they are robust, survive treatment and endure prolonged storage conditions. Several studies involving the role of miRs in cHL have been reported [42][43][44][45][46][47][48], but very few in the context of an HIV-1 infection [49].…”
Section: Discussionmentioning
confidence: 99%
“…Difference of the miRNA expressions has been implicated in various malignancies and several miRNAs have been determined associated with pathogenesis of some cancers (13)(14)(15)(16)(17)(18)(19). But there is relatively a few studies reported miRNA expression status in HLs (20)(21)(22)(23)(24). In a recent study, Sánchez-Espiridión et al (21) (11,20,25).…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly, miR-23a, miR-122, miR-93, and miR-144 [ 199 ], miR-582-3p, miR-525-3p, miR-448, miR-512-3p, miR-642a-5p, miR-876-5p, miR-532-3p, miR-654-5p, miR-128, miR-145-5p, miR-15b-5p, miR-328, and miR-660-5p were designated as downregulated [ 200 ]. Other studies that are based on a limited number of samples have no information about age [ 201 ], used data miming [ 202 ], or are centered on different cell lines that are all of adult origin [ 203 , 204 , 205 , 206 ]. Thus, so far, there is no information about dysregulated miRNAs in the pediatric setting.…”
Section: Lymphomasmentioning
confidence: 99%